2003
DOI: 10.1143/jjap.42.1496
|View full text |Cite
|
Sign up to set email alerts
|

Response of Piezoelectric Lead–Zirconate–Titanate to Hypervelocity Silver Particles

Abstract: A short review of the properties of electron distribution functions in a fully ionized plasma in the presence of high-frequency laser radiation is given. Weak and strong field situations are considered. In a weak field, when the amplitude of the electron quiver velocity in the field is smaller than the electron thermal velocity, the distributions of both the thermal and the under thermal electrons are considered. The conditions are shown when it is necessary to take into account the deviation of the electron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It was also found that the sensitivity of the fourteen-layered detector was higher than that of a hundred-layered detector in this experiment. These results are useful for the application of PZT not only to radiation detectors but also to cosmic dust monitors onboard a satellite [12][13][14][15][16]. On the other hand, further investigation is required to determine the production mechanism of the acoustic signal in piezoelectric PZT.…”
Section: Discussionmentioning
confidence: 97%
“…It was also found that the sensitivity of the fourteen-layered detector was higher than that of a hundred-layered detector in this experiment. These results are useful for the application of PZT not only to radiation detectors but also to cosmic dust monitors onboard a satellite [12][13][14][15][16]. On the other hand, further investigation is required to determine the production mechanism of the acoustic signal in piezoelectric PZT.…”
Section: Discussionmentioning
confidence: 97%
“…These experiments were conducted at the University of Tokyo and Max-Planck-Institut fü r Kernphysik (MPI-K), and the results obtained so far were as follows (described in full in Miyachi et al, 2003Miyachi et al, , 2004Miyachi et al, , 2005a. When the output voltage obtained from the PZT detector appeared immediately after the collision, it was found that the output waveform was explicitly related to the particle's velocity on impact.…”
Section: Introductionmentioning
confidence: 99%
“…We have been developing a cosmic dust detector using a lead zirconate titanate (PZT) target for use onboard the spacecraft (Miyachi et al, 2003(Miyachi et al, , 2004(Miyachi et al, , 2005a. PZT is a piezoelectric ceramic.…”
Section: Introductionmentioning
confidence: 99%